2017
DOI: 10.3831/kpi.2017.20.021
|View full text |Cite
|
Sign up to set email alerts
|

Review on Clinical Trials of Black Seed (Nigella sativa ) and Its Active Constituent, Thymoquinone

Abstract: ObjectivesNigella sativa (black seed or black cumin), which belongs to the Ranunculacea family, is an annual herb with many pharmacological properties. Among its many active constituents, thymoquinone (TQ) is the most abundant constituent of the volatile oil of Nigella sativa (N. sativa) seeds, and it is the constituent to which most properties of this herb are attributed.MethodsPubMed-Medline, Scopus, and Web of Science databases were searched to identify randomized control trials (RCTs) investigating the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(74 citation statements)
references
References 72 publications
2
69
0
3
Order By: Relevance
“…The safety and efficacy of N sativa used for many human diseases has been established in several randomized clinical studies. 7 We also used N sativa oil in a randomized, double-blind placebo-controlled trial on asthmatic patients with acceptable safety and efficacy profile. 8 Moreover, several meta-analyses have confirmed the beneficial effects and safety of N sativa on hyperlipidemia, type 2 diabetes, obesity, hypertension, and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy of N sativa used for many human diseases has been established in several randomized clinical studies. 7 We also used N sativa oil in a randomized, double-blind placebo-controlled trial on asthmatic patients with acceptable safety and efficacy profile. 8 Moreover, several meta-analyses have confirmed the beneficial effects and safety of N sativa on hyperlipidemia, type 2 diabetes, obesity, hypertension, and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nigella sativa is well-known traditional medicine in the middle east that is used to treat chronic cardiovascular, hepatic, and renal diseases. 4 Most of the pharmacological properties in this seed is attributes to its quinine derivative known as thymoquinone (TQ). 5 TQ has been well known for its diverse therapeutic properties including antimicrobial, antioxidants, and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Molla et al (2019) described the anti-viral activity of Nigella sativa and its constituents against several human, animals, birds and plant pathogenic viruses, such as murine cytomegalovirus infection, avian influenza (H9N2), Schistosoma mansoni infection, PPR virus, broad bean mosaic virus, HIV, hepatitis C virus, zucchini yellow mosaic virus, and papaya ring spot virus, suggesting that Nigella sativa may be one of the best sources of anti-viral drugs [187]. Furthermore, N. Sativa has been established as a safe herbal product [188]. Clinical trials using black seed and its active constituent, TQ, revealed that their administration did not cause liver, kidney, or gastrointestinal side effects [189,190].…”
Section: Thymoquinonementioning
confidence: 99%